Lumbar Herniation of Kidney following Iliac Crest Bone Harvest - Michael Justin Willcox (Case Reports in Surgery)
The iliac crest is a popular source for autogenous bone harvesting, but the process is rife with complications. This case report presents a patient that experienced incisional lumbar herniation of her kidney following an iliac crest bone harvesting procedure. A discussion is included on the underappreciated complications of this procedure and recommendations for improving outcomes with more thorough evaluation and documentation.